2013
DOI: 10.1177/1028315313496572
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization at Home Alternatives to Study Abroad

Abstract: Colleges and universities are increasingly internationalizing their curricular and cocurricular efforts on campuses; subsequently, it is important to compare whether internationalization at home activities may be associated with students' self-reported development of global, international, and intercultural (GII) competencies. This study examined undergraduate students' participation in study abroad and on-campus global/ international activities within nine large public research universities in the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(96 citation statements)
references
References 39 publications
3
73
0
1
Order By: Relevance
“…Internationalization efforts at home have also shown that students may develop intercultural competencies without the burden of traveling to a foreign country (Baldassar & McKenzie, 2016;Leask, 2004;Lilley, Barker, & Harris, 2015;Nilsson, 2003;Soria & Troisi, 2013). Jones (2013) argues that all students, not just those with international mobility, should enjoy an internationalized curriculum in order to develop transferable skills that will allow them to compete in the current job market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Internationalization efforts at home have also shown that students may develop intercultural competencies without the burden of traveling to a foreign country (Baldassar & McKenzie, 2016;Leask, 2004;Lilley, Barker, & Harris, 2015;Nilsson, 2003;Soria & Troisi, 2013). Jones (2013) argues that all students, not just those with international mobility, should enjoy an internationalized curriculum in order to develop transferable skills that will allow them to compete in the current job market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When universities globalize and internationalize, students need to be equipped with the skills to negotiate these aspects of higher education if they are going to be successful graduates. The classroom is one of the places that the global-self can be developed (Chang, 2006;Urban, 2012;Urban & Palmer, 2014), but activities outside the classroom, where co-curricular learning can be activated, also impact student development (Astin, 1984;Killick, 2015;Kuh, 1993;Soria & Troisi, 2013;Tierney, 1992;Tinto, 1975).…”
Section: Internationalization and Globalizationmentioning
confidence: 99%
“…Soria and Troisi (2013) reviewed student experiences with internationalization at-home activities at nine large public research universities and propose that "internationalization at-home activities can also promote students' development of global, international, and intercultural competencies just as effectively as-if not more effectively than-formal study abroad" (p. 273).…”
Section: Engagementmentioning
confidence: 99%
See 2 more Smart Citations